The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10943-018-0621-3
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality Experiences in Hemophilia Patients: A Phenomenological Study

Abstract: Spirituality plays an important role in coping with chronic diseases. However, the meaning of spirituality is not known in hemophilia, as a chronic disease. This study aimed to explore the essence of spirituality in hemophilia patients. This qualitative study with a hermeneutic phenomenological approach was conducted on twelve Muslim adult hemophilia patients. The participants were selected using purposeful sampling. The data were gathered through interview. Then, the data were analyzed using thematic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…33 Iranian Muslim people had strong spiritual beliefs and used spirituality to cope with chronic diseases. 14 The findings of the present study revealed a relationship between hope and psychological issues, including depression, anxiety, stress, perceived social support, and spiritual well-being. Moreover, the results of regression analysis showed that the associations between hope and anxiety, stress, and perceived social support were statistically significant.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…33 Iranian Muslim people had strong spiritual beliefs and used spirituality to cope with chronic diseases. 14 The findings of the present study revealed a relationship between hope and psychological issues, including depression, anxiety, stress, perceived social support, and spiritual well-being. Moreover, the results of regression analysis showed that the associations between hope and anxiety, stress, and perceived social support were statistically significant.…”
Section: Discussionsupporting
confidence: 49%
“…13 Spirituality was effective in improvement of physical, mental, and social health in chronic diseases. 14 Higher levels of spirituality also led to well-being and moral development. 15 Furthermore, hope was associated with spiritual beliefs and optimism.…”
Section: Introductionmentioning
confidence: 99%
“…43 In this session, some information regarding spiritual support, such as relationship with God, praying for oneself and others, reading Quran, hope in God, trust in God, spiritual satisfaction, and thanking the divine blessing, was also given to the peers. 44 The participants' questions were answered during the sessions and their wrong beliefs were corrected by referring to scientific resources. After all, the booklet of the presented information was given to the peers.…”
Section: Interventionmentioning
confidence: 99%
“…It is not infrequent for patients with hemophilia (whether HIV + or HIV − ) to abuse alcohol and prescribed drugs to relieve their pain. 14 Depression and moodiness have both been used to describe hemophilia patients, especially those who are HIV + or HCV + . It is not clear whether these reported depression and moodiness issues are related to the HIV infection stigma, or they may indeed be an early expression of infection of the central nervous system.…”
Section: Resultsmentioning
confidence: 99%